Pengaruh Latihan Burpee Pass Dan Box Jump Terhadap Power Otot Tungkai Pemain SSB UNTAG ROSITA U-16 Surabaya - Achmad Yazid Fawaid; Ramadhany Hananto Puriana (Jurnal Ilmiah Adiraga, 2024)
This research aims to examine vertical jumps on leg muscle power at SSB Untag Rosita U-16 Surabaya. This research uses quantitative research with experimental methods. In this study, a two-group pretest-posttest design was used, where this design contained a pretest and posttest. The sample in this research was 20 SSB Untag Rosita students. The implementation and data collection in this research used the test method. The statistical analysis methods used are descriptive analysis, normality test, homogeneity test, and t test (paired) using SPSS 25.Based on a series of research activities that have been carried out, it can be said that the Burpee Pass and Box Jump types of training can increase the leg muscle power of SSB Untag Rosita U-16 Surabaya players because the sig. (2-tailed) in the Burpee Pass and Box Jump Homogeneity Test, which is 0.050, so the sig value. (2-tailed) on the leg muscle power of SSB Untag Rosita U-16 Surabaya students there is a significant effect, and the results of the Paired Test on Burpee Training are stated as sig (2-tailed) on the results of posttest 1 < 0.05, so it can be it was stated that the Burpee Pass exercise had an effect on the leg muscle power of the SSB Untag Rosita U-16 Surabaya players and the results of the Paired Test on the Box Jump exercise stated a sig (2-tailed) value on the results of posttest 2 and < 0.05, so it can be stated that the exercise Box Jump affects the leg muscle power of SSB U-16 Surabaya players. Keywords: Burpee Pass, Box Jump, Leg Muscle Power.